2024
DOI: 10.3390/buildings14040960
|View full text |Cite|
|
Sign up to set email alerts
|

FE Model Updating of Continuous Beam Bridge Based on Response Surface Method

Fang Dong,
Zhongqi Shi,
Rumian Zhong
et al.

Abstract: In this paper, A high-order response surface method is proposed for finite element model updating of continuous beam bridges. Firstly, based on visual inspection and environmental vibration testing, the peak picking (PP) method and random subspace identification (SSI) method are used to identify the dynamic characteristic parameters of the structure. Then, the finite element model of the continuous beam bridge is updated based on the third-order response surface method. It can be concluded that the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The response surface method is to fit the regression equation to obtain the functional relationship between the factors and the response value and adjust the optimization test plan to seek the optimal process parameters. The method is a mathematical statistical method for solving multivariate problems [13]. Studies have shown that the response surface method can be effectively applied to the modeling of the flotation process to improve the efficiency of flotation.…”
Section: Introductionmentioning
confidence: 99%
“…The response surface method is to fit the regression equation to obtain the functional relationship between the factors and the response value and adjust the optimization test plan to seek the optimal process parameters. The method is a mathematical statistical method for solving multivariate problems [13]. Studies have shown that the response surface method can be effectively applied to the modeling of the flotation process to improve the efficiency of flotation.…”
Section: Introductionmentioning
confidence: 99%